Medium-assisted van der Waals dispersion interactions involving chiral molecules - Hassan Safari; Pablo Barcellona; Stefan Yoshi Buhmann; A Salam (New Journal of Physics, 2020)
The van der Waals dispersion interaction between two chiral molecules in the presence of arbitrary magnetoelectric media is derived using perturbation theory. To be general, the molecular polarisabilities are assumed to be of electric, paramagnetic and diamagnetic natures, and the material environment is considered to possess a chiral electromagnetic response. The derived expressions of electric dipole polarisable–chiral, magnetic dipole susceptible–chiral, and diamagnetic susceptible–chiral, and chiral–chiral interaction potentials when added to the previously obtained contributions in the literature, form a complete set of dispersion interaction formulas. We present them in a unified form making use of electric–magnetic duality. As an application, the case of two anisotropic molecules embedded in a bulk magnetoelectric medium is considered, where we derive the retarded and non-retarded limits with respect to intermolecular distance.